Loneliness experienced by those providing care for an adult family member with chronic illness - McPherson, Christine J (Evidence-based nursing, 2025)
Implications for practice and research The study describes the social, emotional and existential aspects of loneliness in family caregivers of adults with chronic illnesses who are housebound, raising awareness of a prevalent and significant issue. Context Loneliness is a universal, subjective experience that arises from a perceived lack of meaningful social relationships or connectedness with those around us.1 2 It is characterised by feelings of isolation, emptiness and a sense of disconnectedness from others.1 While feelings of loneliness can be transient, chronic loneliness is pervasive in society and contributes to negative mental and physical health outcomes.2 Family caregivers (CGs) are one group particularly affected by loneliness due to changes in familial roles and responsibilities, and increased demands of the caregiving role.3 The primary aim of Chistell and colleagues’ study4 was to develop a conceptual model of the phenomenon of loneliness among CGs of adult care recipients (CRs) with chronic illnesses who were housebound. No information was reported on the types of chronic illnesses though the length of caregiving was substantial (between 20 months and 25 years).